PEDAGOGICAL ANALYSIS OF PROBLEM OF PROFESSIONAL PREPARATION OF FUTURE ECONOMISTS IS IN UNIVERSITIES OF AZERBAIJAN - Алієв, Октай Керимович (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
In the article the pedagogical to the analysis of problem of professional preparation of future economists is carried out in the universities of Azerbaijan, the factors of development of economic education are reflected in a country, priorities are certain in the improvement of professional preparation of future economists in the universities of Azerbaijan taking into account modern civilization progress trends